(untitled) (Innovaciones Educativas, 2026)
In Costa Rica, the role of personal assistance is recognized in Law 9379 and in its regulation, Executive Decree 41087-MTSS, as a support mechanism to promote autonomy and independent living for people with disabilities. However, there is still no technical profile that specifies the functions, competencies, and ethical values required for this role, which generates limitations in training processes and in the quality of the service provided. Based on the above, the purpose of this study was to analyze the functions, competencies, ethical values, and training gaps linked to personal assistance, considering both the current legal framework and the educational perspective. To this end, a mixed-methods approach was adopted, combining a systematic literature review with the administration of questionnaires to persons with disabilities and to professionals related to this work. The results indicate that socio-emotional skills, together with ethical and legal foundations, constitute the basis of the professional profile, although difficulties persist in the definition of functions, in specialized training, and in service supervision mechanisms. These findings highlight the need to consolidate updated training programs and to promote inclusive public policies. The main contribution of this research lies in generating evidence that may guide educational processes and support the design of public policy guidelines consistent with the social model of disability and with a human rights approach.